Examining the association between neighborhood conditions and school readiness across low and highly segregated school attendance boundaries - Lenahan, Teka; LoCasale-Crouch, Jennifer; Chamberlain, Caroline; Williford, Amanda; Downer, Jason; Whittaker, Jessica; Miller, Luke (Frontiers in Education, 2022)
Neighborhood characteristics are well documented determinants of adolescent and adult health and well-being. One such neighborhood characteristic heavily explored in K-12 research is the role of residential segregation on educational outcomes. Surprisingly, little is known about how community conditions, as well as racial segregation, relate to children’s early school readiness. This is a critical gap in the field as children’s school readiness is a significant marker of school success, both in the short and long term. Thus, this study aimed to address this gap through examining statewide school readiness data and neighborhood opportunity resources related to early childhood development. Student-level readiness data from 84,720 kindergarteners collected through the 2019 Virginia Kindergarten Readiness Program were used to determine whether a student demonstrated school readiness skills. Community conditions surrounding a school were constructed using geospatial mapping of the 2015 School Attendance Boundary (SAB) Survey and Child Opportunity Index 2.0. This study then explored the role of neighborhood segregation in a SAB with student’s school readiness with three separate approaches (entropy, exposure, and share of racial/ethnic groups). A series of logit regression models were used to examine the relationship between community resources and the likelihood a student was school-ready and whether this relationship varied across low and highly segregated SABs. Results indicated that a student in a higher resourced community was more likely to be school ready than a similar student in a lower resourced community. Distribution of students by race/ethnicity across neighborhood resource levels was uneven. Specifically, Black and Hispanic children are overrepresented in lower resourced communities, and White and Asian children overrepresented in higher resourced ones. Further, in two out of three measures of segregation, results show significant variation between neighborhood resources and school readiness likelihood across different levels of segregation. Consistently, students within a more segregated (and particularly Segregated Black or Hispanic) SAB were more sensitive to changes in community resources than those in less segregated SAB. Program and policy implications are discussed.